2014
DOI: 10.1073/pnas.1416747111
|View full text |Cite
|
Sign up to set email alerts
|

A complete Holocene record of trematode–bivalve infection and implications for the response of parasitism to climate change

Abstract: Increasing global temperature and sea-level rise have led to concern about expansions in the distribution and prevalence of complex-lifecycle parasites (CLPs). Indeed, numerous environmental variables can influence the infectivity and reproductive output of many pathogens. Digenean trematodes are CLPs with intermediate invertebrate and definitive vertebrate hosts. Global warming and sea level rise may affect these hosts to varying degrees, and the effect of increasing temperature on parasite prevalence has pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…Due to the effects of climate change, northward range expansions have already occurred in other trematode species, and as global temperatures rise, even greater range expansions are expected (MasComa et al 2008, 2009, Huntley et al 2014. For some parasites, climate change is also predicted to lead to greater disease impact due to an increase in local prevalence (Mas-Coma et al 2008, Huntley et al 2014, Williams & Boyko 2016.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the effects of climate change, northward range expansions have already occurred in other trematode species, and as global temperatures rise, even greater range expansions are expected (MasComa et al 2008, 2009, Huntley et al 2014. For some parasites, climate change is also predicted to lead to greater disease impact due to an increase in local prevalence (Mas-Coma et al 2008, Huntley et al 2014, Williams & Boyko 2016.…”
Section: Discussionmentioning
confidence: 99%
“…For some parasites, climate change is also predicted to lead to greater disease impact due to an increase in local prevalence (Mas-Coma et al 2008, Huntley et al 2014, Williams & Boyko 2016. This is likely related to higher transmission rates caused by an increase in cercarial production response to warming water temperatures (Poulin 2006).…”
Section: Markowitz Et Al: Assay For Proctoeces Maculatus In Mytilusmentioning
confidence: 99%
See 1 more Smart Citation
“…Fossil evidence for parasitic flatworms can be derived from (1) rare exceptionally preserved body fossils, which can be isolated (Poinar and Boucot, 2006;Dentzien-Dias et al, 2013) or remain associated with their hosts (Upeniece, 2001(Upeniece, , 2011 or (2) more commonly occur as characteristic traces or skeletal pathologies in their (intermediate) hosts, which have the potential to be traced back in the fossil record (Ruiz and Lindberg, 1989;Ruiz, 1991;Ituarte et al, 2001Ituarte et al, , 2005Huntley, 2007;Todd and Harper, 2011;Huntley and Scarponi, 2012;Huntley et al, 2014;Huntley and Scarponi, 2015;Huntley and De Baets, 2015). Parasite body fossils are scarce due to their small size, lack of hard parts and the residence within the host and/or isolation from their hosts (Conway Morris, 1981;Littlewood and Donovan, 2003;De Baets et al, 2011).…”
Section: Assessment Of the Flatworm Fossil Recordmentioning
confidence: 99%
“…This is not straightforward since it has been demonstrated that the remains of soft-bodied helminths can be destroyed during the pearl formation process (Lauckner, 1983). However, other pathologies are believed to be more characteristic for particular lineages of parasitic flatworms such as Gymnophallidae including shell pits (Ruiz and Lindberg, 1989;Ruiz, 1991;Huntley, 2007;Todd and Harper, 2011, Figure 1(e); Huntley and Scarponi, 2012;Huntley et al, 2014;Huntley and Scarponi, 2015;Huntley and De Baets, 2015) and volcano-to igloo-shaped calcareous concretions (Campbell, 1985;Ituarte et al, 2001Ituarte et al, , 2005; Figure 2(aec); Huntley and De Baets, 2015). Ituarte et al (2001Ituarte et al ( , 2005) demonstrated a link between igloo-shaped concretions and gymnophallid digenean flatworms, which these authors traced back to 6400 years in the Holocene.…”
Section: Silurian Blister Pearls and Calcareous Concretions In Bivalvmentioning
confidence: 99%